Transparency politics and its limits: rethinking hermeneutical injustice - Clanchy, N (2023)
I draw on work in social epistemology, feminist philosophy, trans philosophy, queer theory, and ethics to rethink what hermeneutical injustices are, who suffers them, and what can be done to prevent them. I identify several problems with Miranda Fricker’s original account of what hermeneutical injustices are and how they arise, and argue for a number of revisions and clarifications in order to solve these problems. One upshot of these revisions is that more people suffer hermeneutical injustices than Fricker’s account acknowledges. I then outline a novel, more materialist sort of strategy for preventing hermeneutical injustices, and argue that the provision of gender-affirming healthcare is one context in which such a strategy ought to be pursued. Finally, I criticize the hermeneutical injustice literature for what I call its implicit commitment to transparency politics. By this I mean its implicit commitment to the view that when it comes to the hermeneutical dimension of people’s lives, the satisfaction of their interests in things about themselves being intelligible is all that matters. I argue that this view is mistaken, not least because it ignores the existence of two other important sorts of distinctly hermeneutical interest.